189k views
5 votes
What transformation takes the graph of f(x)=3x+8 to the graph of g(x)=3x+6​

What transformation takes the graph of f(x)=3x+8 to the graph of g(x)=3x+6​-example-1
User Cody Hess
by
5.7k points

1 Answer

4 votes

Answer: D) 2 units down

==================================================

Work Shown:

f(x) = 3x+8

g(x) = 3x+6

g(x) = 3x+6+0 .... adding on 0 doesn't change anything

g(x) = 3x+6+2-2 ... replace 0 with 2-2

g(x) = (3x+6+2)-2

g(x) = (3x+8)-2

g(x) = f(x)-2 ... replace 3x+8 with f(x)

The last line shows that g(x) is the result of shifting f(x) down 2 units.

Recall that y = f(x). When we say f(x)-2, we mean y-2. So we subtract 2 from every y coordinate, which is why the f(x) graph moves down 2 units.

User Vambo
by
5.5k points